Does Female Human Capital Matter for Economic Growth in a Developing Country? (Journal of Social Sciences Review, 2023)
This study explores the importance of human capital on economic growth from gender perspective in Pakistan. To proxy human capital, two indices are constructed for male and female separately i.e. health capital and education capital. The study uses ARDL bound test and found cointegration between human capital and economic growth. In the long-run, human capital encourages economic growth regardless of gender specific human capital or type of human capital while in short-run gender specific human capital is more rewarding. Further, granger’s causality results reveal two-way causation between gender specific human capital and economic growth for both male and female using health proxy for human capital while there is no causality between human capital (male/education) and economic growth.
Keywords: Economic Growth; Female Human Capital; Health; Education